CLASSROOM MANAGEMENT IN IMPROVING LEARNING EFFECTIVENESS IN PUBLIC ELEMENTARY SCHOOL 57 BANDA ACEH - Hartati, Sri; Sari, Siti Mayang (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of writing this article is to examine classroom management in improving the effectiveness of learning at SD Negeri 57 Banda Aceh. The method used is descriptive qualitative with data collection techniques through direct observation at SD Negeri 57 Banda Aceh. The results of the study indicate that the implementation of effective classroom management, such as optimal classroom arrangements, consistent discipline, and good communication between teachers and students, plays an important role in creating a conducive learning environment. In addition, strategies such as the use of learning media and time management techniques have also been shown to increase student involvement in the learning process. The implementation of structured and consistent classroom management not only creates a better learning environment but also plays an important role in improving student learning outcomes. These findings provide empirical evidence of the importance of effective classroom management in the context of elementary education and can be used as a reference for classroom management practices in other schools.